IMPACT OF AUTOMATION ON EMPLOYMENT IN DEVELOPING VS DEVELOPED COUNTRIES - Loso Judijanto; Hadenan Towpek (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyse and compare the impact of automation on employment in developing and developed countries. The literature review is conducted by examining various scientific literature, reports of international organisations, and secondary data related to changes in the structure of employment due to the adoption of automation technology. The results show that developed countries are generally better prepared for digital transformation thanks to adequate infrastructure, adaptive education systems, and progressive labour policies. Automation in developed countries tends to create new job opportunities in the technology and services sectors, although it still requires an increase in labour skills. In contrast, in developing countries, automation has the potential to cause greater disruption to employment, particularly in labour-intensive and informal sectors, due to limited access to education, training and digital infrastructure. The study concludes that to minimise the negative impacts of automation and maximise the opportunities, developing countries need to accelerate investment in education, digital skills training, and strengthening inclusive labour policies. The findings are expected to serve as a reference for policymakers and stakeholders in formulating adaptive labour strategies in the era of automation.